Pengaruh Lingkungan Keluarga, Fasilitas Belajar dan Kemandirian Belajar terhadap Hasil Belajar Siswa Kelas X dan IX IPS pada Mata Pelajaran Ekonomi - Rizki Rabiah; Rita Syofyan (Jurnal Salingka Nagari, 2023)
The purpose of this study was to determine the effect of family environment, learning facilities and independent learning on the learning outcomes of class X and IX students in economics subjects SMA Negeri 2 Painan students during the Covid-19 pandemic. This type of research was an associative descriptive study with a population of 231 SMA Negeri 2 Painan. The sampling technique is proportional random sampling with a sample of 35 students. Data collection techniques are carried out by distributing questionnaires. To ensure the questionnaire used in this study, validity and reliability tests were used. The data analysis technique used is multiple regression analysis with the help of SPSS 15.0. Before performing the data analysis technique, the classical assumption test is carried out using the normality test and homogeneity test. The results of the research The results showed that 1) the family environment have a positive and no significant effect on learning outcomes, 2) learning facilities have a positive and no significant effect on learning outcomes, 3) learning independence had a positive and no significant effect on learning outcomes 4) family environment, learning facilities and independent learning together has a positive and insignificant effect on student learning outcomes